Modul Pembelajaran Plta Berbasis Augmented Reality - Yessy Asri; Alvin Kurnia Niwes (KILAT, 2016)
Hydroelectric Power Plant (HEPP) is one plant that uses water flow to be converted into electrical energy. This power plant works by changing the energy of water flowing (from dam or waterfall) into mechanical energy (with the help of water turbines) and of the mechanical energy into electrical energy (with the help of a generator). The electrical energy then flowed through networks that have been made, until finally the electrical energy to the consumer. Hydropower has five main components, namely dams, turbines, generators, penstock, and track transmisi..Augmented Reality is a technology that combines virtual objects are two-dimensional or three-dimensional environment into a real three. This study uses a multimedia development stage is done by six stages, namely the concept, design, collecting, assembly, testing, and distribution. Application of Augmented Reality as a learning medium hydroelectric plants which can visualize the turbine and generator in 3D. Manufacture and design of 3D objects is done by using software blender. Then this object is inserted into the Unity 3D that can be viewed when the marker is detected.